2010
DOI: 10.1016/j.freeradbiomed.2010.01.038
|View full text |Cite
|
Sign up to set email alerts
|

Redox-mediated reciprocal regulation of SERCA and Na+–Ca2+ exchanger contributes to sarcoplasmic reticulum Ca2+ depletion in cardiac myocytes

Abstract: Myocardial failure is associated with increased oxidative stress and abnormal excitation-contraction coupling characterized by depletion of sarcoplasmic reticulum (SR) Ca 2+ -stores and a reduction in Ca 2+ -transient amplitude. Little is known about the mechanisms whereby oxidative stress affects Ca 2+ -handling and contractile function; however, reactive thiols may be involved. We used an in vitro cardiomyocyte system to test the hypothesis that short-term oxidative stress induces SR Ca 2+ -depletion via red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
89
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(95 citation statements)
references
References 29 publications
5
89
0
1
Order By: Relevance
“…In addition, ROS induced decreased cytosolic Ca + 2 associated with decreased activity of L-type Ca 2 + channels (100) and RyRs (287), or increased activity of NCX (219) has also been shown in other studies, and this may cause shortening of the action potential followed by loss of excitability as shown by Jabr and Cole (126). The contradictory results on ROS effects on ion channels and the action potential might be due to species differences (44,276) in the concentration (89) and the type of ROS involved (41) and the number and type of channels affected (12,149). In support of this idea, Tokube et al (250) reported ROS-induced biphasic changes in the action potential duration, with initial lengthening of the action potential due to a rapid decrease in whole-cell I K and subsequent shortening due to a decrease of whole-cell I Ca and increase in ATP-sensitive outward K + current (I KATP ).…”
Section: Overview Of Ros Effects On Cardiac Ion Currents Actionmentioning
confidence: 82%
See 1 more Smart Citation
“…In addition, ROS induced decreased cytosolic Ca + 2 associated with decreased activity of L-type Ca 2 + channels (100) and RyRs (287), or increased activity of NCX (219) has also been shown in other studies, and this may cause shortening of the action potential followed by loss of excitability as shown by Jabr and Cole (126). The contradictory results on ROS effects on ion channels and the action potential might be due to species differences (44,276) in the concentration (89) and the type of ROS involved (41) and the number and type of channels affected (12,149). In support of this idea, Tokube et al (250) reported ROS-induced biphasic changes in the action potential duration, with initial lengthening of the action potential due to a rapid decrease in whole-cell I K and subsequent shortening due to a decrease of whole-cell I Ca and increase in ATP-sensitive outward K + current (I KATP ).…”
Section: Overview Of Ros Effects On Cardiac Ion Currents Actionmentioning
confidence: 82%
“…Indeed, ROS-induced membrane depolarization occurred with increased Na + window current (the window current results from the overlap of activation and inactivation steady-state curves due to depolarized membrane voltages that are sufficient to transiently open a few available channels) (27), increased activity of NCX (90), inhibition of the inward I K (199), activation of an inwardly directed nonselective cationic current (182), increased intracellular Ca + 2 concentration associated with increased activity of the L-type Ca + 2 channels (117) or ryanodine receptors (RyRs) (9), and decreased activity of the sarcoplasmic reticulum (SR) Ca 2 + pump SERCA2a (149). An example from guinea pig myocytes (Fig.…”
Section: Overview Of Ros Effects On Cardiac Ion Currents Actionmentioning
confidence: 99%
“…To see this illustration in color, the reader is referred to the web version of this article at www.liebertpub.com/ars (125). Consistent with this increase in activity with HF, ROS has also been shown to increase NCX activity via oxidation (59,100,130). However, there is a negative consequence of this increased NCX activity, which is to increase the propensity to generate arrhythmias (7).…”
Section: Sr Ca 2 + -Atpasementioning
confidence: 76%
“…With the enhanced b-AR drive and increased epi/norepi in HF, MAO activity and expression (both MAO A and B) are increased resulting in enhanced H 2 O 2 levels (86,87). In addition, under certain conditions (as occurs in HF), NO production via NOS is interrupted resulting in the production of O 2 -, termed NOS uncoupling (154 (60,61,64,67,100,109,121). These effects of ROS on myocyte Ca 2 + handling are similar to what is observed in failing myocytes.…”
Section: Redox Signalingmentioning
confidence: 99%
“…Lactate production or removal controlled by lactate dehydrogenase (LDH), affects the NAD ϩ /NADH ratio, which in turn affects GSH/GSSG status. Altered GSH/GSSG will affect the critical thiol regulatory proteins (214), including sarcoendoplasmic reticulum Ca ϩϩ ATPase (SERCA) (60,116), and transcription factors such as CREB, known to have two activity-determining thiols (79), causing changes in gene transcription. Changes in SERCA activity will affect calcium homeostasis that in turn will affect gene expression through the calcineurin-nuclear factor of activated T cells (NFAT) pathway (43).…”
Section: The Dynamic Range Of Lactate Signaling In Activation Of Thementioning
confidence: 99%